2018
DOI: 10.1016/j.biocontrol.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context does not constrain biological control of Phenacoccus manihoti in intensified cassava systems of southern Vietnam

Abstract: Landscape context does not constrain biological control of Phenacoccus manihoti in intensified cassava systems of southern Vietnam The International Center for Tropical Agriculture (CIAT) believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture. CIAT is committed to creating and sharing knowledge and information openly and globally. We do this through collaborative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 62 publications
(78 reference statements)
1
33
0
Order By: Relevance
“…The field survey of P. manihoti and A. lopezi was carried out during the dry season of 2017 (October-November) and 2018 (September-October) in 80 cassava fields in Lampung (n = 11 fields), Banten (n = 9 fields), West Java (n = 9 fields), Central Java (n = 9 fields), East Java (n = 12 fields), West Nusa Tenggara (n = 9 fields), and East Nusa Tenggara (n = 21 fields). Survey protocols followed those that have been used in the region (Graziosi et al 2016;Wyckhuys et al 2018a;Le et al 2018), and was focused on cassava fields having characteristics of monoculture, uniform age and a continuous planting throughout the year. We selected older fields (7-10 months of age) with a minimum size of 0.25 ha in the main cassava-growing areas of each province, with individual sites located at least 1 km apart.…”
Section: Field Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The field survey of P. manihoti and A. lopezi was carried out during the dry season of 2017 (October-November) and 2018 (September-October) in 80 cassava fields in Lampung (n = 11 fields), Banten (n = 9 fields), West Java (n = 9 fields), Central Java (n = 9 fields), East Java (n = 12 fields), West Nusa Tenggara (n = 9 fields), and East Nusa Tenggara (n = 21 fields). Survey protocols followed those that have been used in the region (Graziosi et al 2016;Wyckhuys et al 2018a;Le et al 2018), and was focused on cassava fields having characteristics of monoculture, uniform age and a continuous planting throughout the year. We selected older fields (7-10 months of age) with a minimum size of 0.25 ha in the main cassava-growing areas of each province, with individual sites located at least 1 km apart.…”
Section: Field Surveymentioning
confidence: 99%
“…Abundance of cassava mealybug ranged from 10.21 insects per tip in Lampung up to 43.89 insects per tip in East Nusa Tenggara. Le et al (2018) reported that fieldlevel incidence of P. manihoti in Vietnam averaged 24.8% and mealybug abundance averaged 5.56 insects per tip. Higher infestation in some locations, especially in East Nusa Tenggara, was allegedly due to hot weather conditions and lack of intensive cassava cultivation.…”
Section: Distribution and Infestation Of P Manihotimentioning
confidence: 99%
“…For example, slightly higher P. manihoti population levels were recorded in settings with sandy, low-fertile soils (Wyckhuys et al, 2017a) and biological control under those conditions merits closer research attention. Also, as landscape composition and plant disease infection status equally modulate P. manihoti performance and efficacy of biological control at local scale (Wyckhuys et al, 2017b;Le et al, 2018), further replicated trials could be warranted to validate the robustness of our findings under varying agro-ecological contexts. Despite the above confounding factors, careful analysis of production statistics and commodity market fluxes (as in section iv) support our empirical results and confirm A. lopezi to be the major biotic factor affecting mealybug population growth.…”
Section: Discussionmentioning
confidence: 73%
“…Exclusion cage assays illustrated how biological control enabled a root yield recovery of 5.3-10.0 t/ha in two main cassava varieties, and how 2015 yields under 'no cage ' (i.e., 'real-world') conditions were in line with historic in-country yield tendencies. Though no direct field-level measurements were made of A. lopezi parasitism during the cage trials, biological control was found to occupy a central role in lowering P. manihoti populations (Thancharoen et al, 2018), and A. lopezi is a determining factor in ensuring mealybug suppression in other key cassavagrowing areas in Southeast Asia (Le et al, 2018). Cage trials also showed large variability in responses between the two cassava clones, likely reflective of differences in plant vigor and an individual clone's photosynthetic capability (Connor et al, 1981;Cock et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Research Abduchalek et al (2017) studied that Cassava mealybug pest has spread widely in Java. Cassava mealybug pest Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) is one of the cassava pests originating from South America, reportedly entered Africa in early 1970s with a yield loss of 82% (Chakupurakal et al, 1994;Bertschy et al, 2001;Neuenschwander, 2001;Zeddies et al, 2001;Hennessey and Muaka, 2011;Muniappan et al, 2011) and Asia in 2008, it entered Thailand and spread to Cambodia, Laos and Vietnam (Parsa et al, 2012;Sartiami et al, 2015;Le et al, 2018;Upadhyay et al, 2018;Wyckhuys et al, 2018). Pests are thelytokous parthenogenetic which can reproduce all females off spring (Calatayud et al, 2017).…”
Section: Introductionmentioning
confidence: 99%